The Nutrition Advantage: Harnessing nutrition co-benefits of climate-resilient agriculture - Chakrabarti, Soma; Dinesh, Dhanush; Garrett, James (International Fund for Agricultural Development, 2017)
Climate change and malnutrition are among the greatest problems in the twentyfirst century; they are “wicked problems”, difficult to describe, with multiple causes, and no single solution. The impacts of climate change have become evident in crop, livestock and fisheries systems, threatening all aspects of food security, including access, utilization and price stability (Porter et al., 2014). On the other hand, malnutrition, including undernutrition, overnutrition and micronutrient deficiencies, is having devastating impacts on global health and economy. In this report, we examine how investments in climate-resilient agriculture can be leveraged not only to deliver benefits to secure food security under a changing climate, but also to contribute to efforts to eradicate malnutrition.